Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1039/d2cy00538g
|View full text |Cite
|
Sign up to set email alerts
|

Liquid phase catalytic transfer hydrogenation of ethyl levulinate to γ-valerolactone over ZrO2/SBA-15

Abstract: γ-Valerolactone (GVL) is an important bio-derived platform molecule whose atom- and energy efficient, and scalable, catalytic synthesis is highly desirable. Catalytic transfer hydrogenation (CTH) of ethyl levulinate (EL) to γ-valerolactone...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…[29] and high activity for carboxylic acid esterification, [30] including of LA formed in-situ from glucose. [31] Our recent work on ZrO 2 /SBA-15 identified this as efficient for the continuous flow CTH of ethyl levulinate CTH to GVL, [32] and hence this was chosen as the (predominantly) Lewis acid catalyst. The optimum catalyst selections delivered a high and stable GVL yield of 80 % at 150 °C in flow, significantly higher than either individual catalyst in flow or a physical mixture in batch.…”
Section: Chemcatchemmentioning
confidence: 99%
“…[29] and high activity for carboxylic acid esterification, [30] including of LA formed in-situ from glucose. [31] Our recent work on ZrO 2 /SBA-15 identified this as efficient for the continuous flow CTH of ethyl levulinate CTH to GVL, [32] and hence this was chosen as the (predominantly) Lewis acid catalyst. The optimum catalyst selections delivered a high and stable GVL yield of 80 % at 150 °C in flow, significantly higher than either individual catalyst in flow or a physical mixture in batch.…”
Section: Chemcatchemmentioning
confidence: 99%
“…Because of advantages in terms of cost and reagent safety, continuous reduction via catalytic hydrogen transfer has also been also reported. In-flow transfer hydrogenation (TH) reactions have already been reported for the reduction of ketones and imines, olefins, and levulinates in order to obtain high-value products, while several studies reported the TH reactions of nitrobenzenes under continuous flow. Based on our knowledge, hydrides have been studied as hydrogen donors in large excess, Au/NaBH 4 and Pd/NaBH 4 have been reported in this field, and Pd/C has been also used with a large excess of ammonium formate and of cyclohexene .…”
Section: Introductionmentioning
confidence: 99%